The Wreck of the Tcheluskin (Polar Record, 1934)
The Tcheluskin expedition left Murmansk on August 10, 1933, with the object of completing a navigation of the North-East Passage both ways, if possible, during one season; and of proving that such a voyage is practicable for a cargo vessel of the type of the Tcheluskin . It is hoped that eventually there may be a regular service of cargo boats on this route, and experiments, with this end in view, have been carried out for several years under the auspices of the Chief Administration of the Northern Sea Route. An account of the expedition, up to the end of December, 1933, when the vessel became beset in the ice, appeared in The Polar Record , No. 7.